Once bitten, twice shy? Market size affects the effectiveness of a leniency program by (de-)activating hysteresis effects - Eva Tebbe (ZBW – Leibniz-Informationszentrum Wirtschaft, 2018)
This article presents results of a laboratory experiment testing whether the effectiveness of a moderate leniency program depends on market size. Against theory, the results indicate that a moderate leniency program is not preferable to a policy which only includes fines for detected cartels, either in duopolies or in quadropolies. Surprisingly, the leniency program is not even entirely to be preferred compared to a laissez-faire policy. Yet, the leniency program seems to work better in markets involving four firms, compared to markets with two firms, especially in terms of the prevention of hysteresis effects.
Keywords: C9; D3; D4; L1; L4; 330; Cartels; Corporate Leniency Program; Experiments; Hysteresis effect; Chat-hysteresis; Bertrand game